PENDIDIKAN POLITIK DARI PERISTIWA 28 JANUARI 2010 - ., Pitoyo (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
A Significant lesson were given by workers’ demonstration that happened on the 28th of January 2012. Different opinion was allowed in the system of democracy, however the government should the differences so that the both parties were satisfied the workers’ demonstration sent messages to government, but. The facts showed that Government leaves the differences run in its own way. This is often called wild cat politic. The consequences of such a policy would , next time, push a bigger demonstration with the possibilities of chaostic. This must be the wrong practice of demo eracy